Epithelial cyst of the spleen - Garima Daga; Varun Mittal; R J Singh; Neena Sood (Wolters Kluwer Medknow Publications, 2011)
This is a report of a case of epithelial cyst of the spleen in an 8-year-old boy. The cyst showed squamous metaplasia on histology. The risk of malignant transformation is discussed.